Predisposing factors and neonatal outcomes for twin-twin transfusion syndrome cases developing transient donor hydrops after fetoscopic laser coagulation: a case control study - Yao-Lung Chang; An-Shine Chao; Shuenn-Dyh Chang; Wen-Fang Li; Po-Jen Cheng (BMC Pregnancy and Childbirth, 2019)
Abstract Background Transient donor hydrops (TDH) is defined as donor hydrops developed within days after laser therapy for twin–twin transfusion syndrome (TTTS) followed by resolution later. The purpose of this study was to evaluate the incidence, neonatal outcomes and predisposing factors of post laser therapy TDH in severe TTTS. Methods A total of 142 patients with severe TTTS who received laser therapy were included into this study. The pre-operative characteristics and neonatal outcomes were compared between TTTS with and without post laser therapy TDH. All live neonates received cranial ultrasound examination after delivery, mild cerebral injury was defined as exhibiting at least one of the following: intraventricular hemorrhage (IVH) grade I and II, lenticulostriate vasculopathy and subependymal pseudocysts; severe cerebral injury comprised at least one among the following: IVH grade III or grade IV, cystic periventriculoleukomalacia (PVL) grade II or more, porencephalic cysts, and ventricular dilatation. Fetal survival was defined as living more than 30 days after delivery. Results